The role of women in communication teaching and research: analysis of university programs in Spain - García-Jiménez, Leonarda (2022)
This article analyzes the role of women in communication research. It does so by studying their presence/absence in the bibliographies of the syllabus of 108 theoretical courses of journalism degrees taught in 36 colleges in Spain during the 2020-2021 academic year. The work investigates the roles and presences of women in the field of communication, measuring the degree of visibility of women scientists and their contributions in a statistical and comparative way to that of male researchers, quantifying the citation patterns according to the gender of the authors. The data were analyzed with the free statistical software R (version 4.0.3) and a descriptive and inferential analysis was performed. The main results regarding the citation patterns of the research are: 1) an under-citation of publications written by female scientists; 2) an over-citation of publications by male researchers; and 3) the non-existence of gender homophily (researchers do not tend to cite more authors of their same gender), since female authors are little cited and this low visibility is due to both female and male faculty members. The most referenced author is Elizabeth Noelle-Neumann, one of the few "classics" present, indicating a Matilda effect regarding the historical erasure of female contributions. In conclusion, the paper argues for the need to transform not only citation practices, but an entire scientific culture that denies women as a source of reference and authority from the early stages of university education.